Жемчужины Филда: ист. проза / Юрий Давыдов - Давыдов Юрий Владимирович (Вагриус, 1999)
Экземпляры: КХ (20020404) / Инвентарный номер: 1043815 / Цена: / Сис.шифр: Р2 / Авт.знак: Д 13 / ГРНТИ: 17 / ББК: 84(2)